Human Dignity, Misthanasia, Public Health and Bioethics in Brazil (Revista Iberoamericana de Bioética, 2017)
This paper aims to reflect on human dignity and misthanasia in the public health system in Brazil. For this, concepts, document reviews and public data about the condition of the Brazilian population’s access to public health were all used. The indicators show the health inequalities in the country, with the north and northeast at a disadvantage both in terms of access to health and the number of available professionals. Thus, the most underserved population tends to continue to be excluded from society and impaired with respect to their human dignity.
Keywords: human dignity; misthanasia; public health; bioethics